Degradation of ribosomal and chaperone proteins is attenuated during the differentiation of replicatively aged C2C12 myoblasts. Issue 5 (12th July 2022) - Brown, Alexander D.; Stewart, Claire E.; Burniston, Jatin G.
Abstract: Background: Cell assays are important for investigating the mechanisms of ageing, including losses in protein homeostasis and 'proteostasis collapse'. We used novel isotopic labelling and proteomic methods to investigate protein turnover in replicatively aged (>140 population doublings) murine C2C12 myoblasts that exhibit impaired differentiation and serve as a model for age‐related declines in muscle homeostasis. Methods: The Absolute Dynamic Profiling Technique for Proteomics (Proteo‐ADPT) was used to investigate proteostasis in young (passage 6–10) and replicatively aged (passage 48–50) C2C12 myoblast cultures supplemented with deuterium oxide (D2 O) during early (0–24 h) or late (72–96 h) periods of differentiation. Peptide mass spectrometry was used to quantify the absolute rates of abundance change, synthesis and degradation of individual proteins. Results: Young cells exhibited a consistent 25% rise in protein accretion over the 96‐h experimental period. In aged cells, protein accretion increased by 32% ( P < 0.05) during early differentiation, but then fell back to baseline levels by 96‐h. Proteo‐ADPT encompassed 116 proteins and 74 proteins exhibited significantly ( P < 0.05, FDR < 5% interaction between age × differentiation stage) different changes in abundance between young and aged cells at early and later periods of differentiation, including proteins associated with translation, glycolysis, cell–cell adhesion, ribosomal biogenesis, and the regulation of cell shape. During early differentiation, heat shock and ribosomal protein abundances increased in aged cells due to suppressed degradation rather than heightened synthesis. For instance, HS90A increased at a rate of 10.62 ± 1.60 ng/well/h in aged which was significantly greater than the rate of accretion (1.86 ± 0.49 ng/well/h) in young cells. HS90A synthesis was similar in young (21.23 ± 3.40 ng/well/h) and aged (23.69 ± 1.13 ng/well/h), but HS90A degradation was significantly ( P = 0.05) greater in young (19.37 ± 2.93 ng/well/h) versus aged (13.06 ± 0.76 ng/well/h) cells. During later differentiation the HS90A degradation (8.94 ± 0.38 ng/well/h) and synthesis (7.89 ± 1.28 ng/well/h) declined and were significantly less than the positive net balance between synthesis and degradation (synthesis = 28.14 ± 3.70 ng/well/h vs. degradation = 21.49 ± 3.13 ng/well/h) in young cells. Conclusions: Our results suggest a loss of proteome quality as a precursor to the lack of fusion of aged myoblasts. The quality of key chaperone proteins, including HS90A, HS90B and HSP7C was reduced in aged cells and may account for the disruption to cell signalling required for the later stages of differentiation and fusion.